Alternative Fiber Sources from Gracilaria Sp and Eucheuma Cottonii for Papermaking - M. Nizar Machmud; Fauzan Fadi; Zahrul Fuadi; Coco Kokarkin (International Journal of Science and Engineering, 2014)
Private sectors have invested in the technology to grow some Gelidialian red algae families and also tried to convert the algae to pulp and paper over the last few years in order to replace raw materials from wood. Several modern systems with their all complexities which are similar to the wood pulp-based papermaking technology have been offered to overcome any recent issues settle in the converting process. Chemical bleaching agents have even been still a standard treatment that must be established for properly converting the algae pulp to a sheet of paper. In this present work, the two genus of red algae, called Gracilaria and Eucheuma, were simply processed to make pulps without use of any bleaching chemical agents. The potential use of pulps made of the red algae as raw materials for papermaking was mechanically studied by testing the sheets made of the red algae through a tensile test at a room temperature under 20 mm/min according to ASTM D 828-97 (2002). Tensile properties of the proposed algae-based paper sheets obtained under the constant rate are discussed. Tensile properties of the selected wood-based paper sheets obtained under the same condition are also presented in this paper. The results showed that pulps made of the red algae would be the alternative to those of the wood and other natural fibers as raw materials for papermaking. Doi: 10.12777/ijse.6.1.1-10 [How to cite this article: Arham, N.A., Mohamad, N.A.N., Jai, J., Krishnan, J., Noorsuhana Mohd Yusof, N.M. (2013). Application of Response Surface Methodology in Extraction of Bioactive Component from Palm Leaves (Elaeis guineensis). International Journal of Science and Engineering, 6(1),1-10. Doi: 10.12777/ijse.6.1.1-10